Dialektika Fiqih Kontemporer Terhadap Ketetapan Hukum Lavender Marriage - Ritonga, Sylvia Kurnia (Syekh Ali Hasan Ahmad Addary State Islamic University, 2024)
Marriage should not cause one of the partners to lose happiness due to wanting to cover up the sexual identity of one of the partners. Contemporary Islamic jurisprudence opens up space in studying the legal status of lavender marriage to avoid marriages that are not in accordance with the maqosid An-nikah. This study is a literature study to reveal the legal status of lavender marriage in the context of contemporary Islamic jurisprudence. Data were obtained by looking in depth at various literatures to get a more specific explanation. The results of this study indicate that lavender marriage is a marriage that is prohibited in Islam because it deviates from the true purpose of marriage. Islamic law does not provide opportunities for marriages that do not respect human nature as men or women in obtaining happiness in marriage. Islam prohibits marriages that violate human nature. Contemporary scholars are not in accordance with the purpose of marriage and violate the rights and obligations of one of the partners.